Recovery after ischemic stroke: Effects of FuekFone home-based program on upper limb and cognitive function - Yaowalak Kumkwan; Ketsarin Utriyaprasit; Thitipong Tankumpuan; Zeng Lertmanorat; Boonyanit Mathayomchan (Elsevier, 2024)
Objectives: This study aimed to explore the effects of the "FuekFone (F.F.) home-based program" on the upper limb and cognitive function of ischemic stroke patients after discharge. Methods: A single group pre-and post-test design was conducted. A total of 40 patients with recovery after ischemic stroke were recruited from two university hospitals in Thailand. The study was conducted between June 2022 and January 2023. Participants underwent a six-week "F.F. home-based program," which combined an upper limb and cognitive function rehabilitation device with Android games, including stationary barrel, adventure walk, adventure stroll, sliding barrel, sauce squeeze, and cut objects. Each game has different difficulty levels. Patients can perform corresponding exercises through the games according to their conditions under the guidance of medical staff. The patients played for 24 min per time, 4 min each game, three days a week. The second week, let the patients play games for 30 min per time, 5 min each game, 3 days a week. Then, in the 3-6 weeks, let the patients play games for 1 h per time, 10 min each game, 5 days a week. At the pre-and post-intervention, the Thai version of the National Institutes of Health Stroke Scale (NIHSS), the Motor Assessment Scale, and the Montreal Cognitive Assessment (MoCA score) were administered to patients at discharge and at 2, 4, and 6 weeksafter discharge, and the results were compared. Results: All participants completed this program. Participants had statistically improved upper limb function (upper arm function score, hand movements score, advanced hand activities score, total Motor Assessment Scale score) and MoCA score at 2, 4, and 6 weeks after discharge (P < 0.001). In the comparison of upper limb function and cognitive function at each of the study times, we found statistically improved upper limb function (upper arm function score, hand movements score, advanced hand activities score, total Motor Assessment Scale score) and MoCA score at 4, and 6 weeks after discharge when compared to after discharge and 2 weeks after discharge, respectively (P < 0.05). Conclusions: Continuing care of patients post-stroke after discharge from hospital, such as F.F. home-based program should be applied at home to enhance upper limb and cognitive function.